I've Got an Idea! Do IDEA Boards Facilitate Improved Completion of Wellness Focused Activities in a College of Nursing? - Jennifer Macali; Cheryl Armstrong (The Ohio State University Libraries, 2021)
Background: In any given academic department there are many ideas discussed to promote wellness, yet it is often difficult to move specific wellness activity ideas from the initial conception stage to the implementation and evaluation stages. Wellness Committees are formed in departments where proposed ideas are generated. However, the same issue of lack of follow-through persists. In order to provide better follow-through and completion of wellness activities, an IDEA board was piloted by a Wellness Committee in a College of Nursing. Aim: This pilot project was implemented to determine the feasibility and utility of using an IDEA board to implement and complete wellness initiatives within a College of Nursing. Methods: An online mixed-methods survey was used to evaluate the use of an IDEA board within a Wellness Committee (n = 9) in a College of Nursing over a one-year period. Results: Results of the pilot study were positive and encouraging. Committee members found the visual representation helpful in guiding the group through the process of idea identification generation to idea implementation and evaluation. Conclusions: Using an IDEA board to guide the process of proposed wellness activities may facilitate improved completion of activities.